EFEKTIVITAS PENGGUNAAN MODEL PEMBELAJARAN STEM TERHADAP LITERASI NUMERASI SISWA SD - Vivi Rulviana; Rissa Prima Kurniawati; Dian Permatasari Kusuma Dayu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
STEM is an interesting learning model. The following research was carried out based on the aim of determining numeracy literacy abilities. This research was carried out with the aim of finding out the effectiveness of using the STEM learning model on students' numeracy literacy abilities. In this research, the samples used were Kleco and Bungkuk Elementary Schools. Data collection in this research used observation, interview and test techniques. In the following research, the T test is used as a hypothesis test. Based on the following research activities, the results showed that the STEM model was effective on the numeracy literacy abilities of elementary school students.